A Phase 2/3 double blinded, randomized, placebo-controlled study in healthy adult participants in Vietnam to examine the safety and immunogenicity of an inactivated whole virion, alum adjuvanted, A(H5N1) influenza vaccine (IVACFLU-A/H5N1). Issue 6 (5th February 2020) - Duong, Tran Nhu; Thiem, Vu Dinh; Anh, Dang Duc; Cuong, Nguyen Phu; Thang, Tran Cong; Huong, Vu Minh; Chien, Vien Chinh; Phuong, Nguyen Thi Lan; Montomoli, Emanuele; Holt, Renee; Scorza, Francesco Berlanda; Flores, Jorge; et al.
Abstract: Background: A global shortfall of vaccines for avian influenza A(H5N1) would occur, especially in low- and-middle income countries, if a pandemic were to occur. To address this issue, development of a pre-pandemic influenza vaccine was initiated in 2012, leveraging a recently established influenza vaccine manufacturing capacity in Vietnam. Methods: This was a Phase 2/3, double-blinded, randomized, placebo-controlled study to test the safety and immunogenicity of IVACFLU-A/H5N1 vaccine in healthy adults. Phase 2 was a dose selection study, in which 300 participants were randomized to one of the three groups (15 mcg, 30 mcg, or placebo). Safety and immunogenicity were assessed in all participants. In Phase 3, 630 participants were randomized to receive the IVACFLU-A/H5N1 vaccine dose selected in Phase 2 (15 mcg, n = 525) or placebo (n = 105). Safety was assessed in all Phase 3 participants and immunogenicity was measured in a subset of participants. Results: The vaccine was well tolerated and most of the adverse events were mild and of short duration. Mild pain at the injection site was the most common adverse event seen in 60 percent of participants in the vaccine group in Phase 3. In Phase 2, both 15 mcg and 30 mcg doses were immunogenic, so the lower dose was selected for further testing in Phase 3. In Phase 3 overall seroconversion rates were 68 percent for hemagglutination inhibition (HI), 51 percent for microneutralization (MN) and 56 percent for single radial hemolysis (SRH). The seroprotection rates were 44 percent for HI, 41 percent for MN and 55 percent for SRH. The GMT ratio was 5.31 and 3.7 for HI and MN respectively; GMA was 4.75 for the SRH. Conclusion: The IVACFLU A/H5N1 was safe and immunogenic. Development of this pandemic avian influenza vaccine is a welcome addition to the limited global pool of these vaccines. ClinicalTrials.gov register NCT02612909.